Dietary patterns are associated with bone mineral density in an urban Mexican adult population. Issue 10 (October 2016) - Denova-Gutiérrez, E.; Clark, P.; Tucker, K.; Muñoz-Aguirre, P.; Salmerón, J.
Abstract Summary Several types of nutrients and foods affect bone mineral density (BMD). However, these nutrients occur together in food groups and dietary patterns, and the overall effects of dietary patterns are not yet well known. Introduction We evaluated the associations between dietary patterns and BMD among adults participating in the Health Workers Cohort Study. Methods In a cross-sectional analysis, we examined 6915 Mexican adults aged 20–80 years. All participants completed a validated self-administered food frequency questionnaire (FFQ) and had total, hip, and spine BMD measurements assessed by dual-energy X-ray absorptiometry (DXA). The FFQ included 116 foods, which were grouped into 22 categories and entered into a factor analysis to derive dietary patterns. Results Three dietary patterns emerged—a Prudent, a Refined foods, and a Dairy and fish pattern. After adjustment for potential confounders, those in the highest quintile of the Prudent pattern had lower odds (OR) of low spine BMD (OR = 0.80; 95 % CI 0.68, 0.94;P for trend = 0.031) compared to those in the lowest quintile. In contrast, participants in the highest quintile of the Refined foods pattern had greater odds of low total BMD (OR = 1.74; 95 % CI 1.10, 2.76;P for trend = 0.016) than those in the lowest quintile. Finally, participants in the highest quintile of the Dairy and fish dietary pattern had significantly lower likelihood of having low BMD. Conclusion This study identified specific dietary patterns associated with BMD among a Mexican adult population and highlights the importance of promoting food-based prevention strategies for maintaining bone health.